The Influence of Regional Government Expenditures on Economic Growth in Gowa Regency 2015-2022 - Ahmad Nur Alanshari (Journal GoodWill, 2024)
This study aims to examine the influence of regional government expenditures on economic growth in Gowa Regency during the period 2015–2022. Using a quantitative approach, this research employs secondary data obtained from the Regional Financial Management Agency and the Central Statistics Agency (BPS) of Gowa Regency. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 26, applying classical assumption tests, simple linear regression analysis, and hypothesis testing. The results reveal that government spending has a positive but statistically insignificant effect on economic growth. The regression coefficient indicates a value of 3.159 with a significance level of 0.20, higher than the 0.05 threshold, suggesting that variations in economic growth cannot be fully explained by government expenditure alone. The coefficient of determination (R²) of 0.625 implies that 62.5% of the variation in economic growth is influenced by government spending, while the remaining 37.5% is determined by other factors beyond the scope of this study. These findings highlight the need for more efficient and targeted fiscal management to enhance the effectiveness of public expenditure in driving regional economic development. Future research should include additional variables such as investment, employment, and inflation to provide a more comprehensive understanding of regional economic growth dynamics.